CHANDRA, KECK, AND VLA OBSERVATIONS OF THE CRAB NEBULA DURING THE 2011-APRIL GAMMA-RAY FLARE - Weisskopf, Martin C.; Tennant, Allyn F.; Arons, Jonathan; Blandford, Roger; Buehler, Rolf; Caraveo, Patrizia; Cheung, Chi C.; Costa, Enrico; De Luca, Andrea; Ferrigno, Carlo; Fu, Hai; Funk, Stefan; et al. (Astrophysical Journal, 2013)
We present results from our analysis of Chandra X-Ray Observatory, W. M. Keck Observatory, and Karl G. Jansky Very Large Array (VLA) images of the Crab Nebula that were contemporaneous with the gamma-ray flare of 2011 April. Despite hints in the X-ray data, we find no evidence for statistically significant variations that pinpoint the specific location of the flares within the Nebula. The Keck observations extend this conclusion to the "inner knot," i.e., the feature within an arcsecond of the pulsar. The VLA observations support this conclusion. We also discuss theoretical implications of the gamma-ray flares and suggest that the most dramatic gamma-ray flares are due to radiation-reaction-limited synchrotron emission associated with sudden, dissipative changes in the current system sustained by the central pulsar.
CRIS-Team WoS Importer:2020-01-15